An economy model for GISMO: DART-PBL technical documentation - Adriana M. Ignaciuk; Sonja Peterson; Michael Hübler; Rob B. Dellink; P.L. Lucas (Netherlands Environmental Assessment Agency, 2009)
The Global Integrated Sustainability Model (GISMO), developed at the Netherlands Environmental Assessment Agency (PBL), is a platform for analysing the complexity of sustainable development and human well-being with regards to the three sustainability domains: People, Planet, and Profit (PPP). The economic structure of the GISMO1.0 model is the International Futures model, developed at the University of Denver. To better address price behaviour in the model, the Computable General Equilibrium (CGE) model DART, developed by the Kiel Institute for the World Economy, was included in the GISMO framework and integrated with the International Futures model. The DART model is tuned to the needs of the GISMO project, and is further referred to as DART-PBL. This report provides an overview of the main changes and additions to the original DART model. The changes and additions include: 1) region and sector aggregation compatible with the GISMO framework; 2) human capital accumulation based on demographics, educational attainment and health level to better address human well-being; 3) introduction of a Linear Expenditure System to distinguish between basic and luxury consumption; 4) adjusted savings to take into account different saving patterns of a changing population structure; 5) heterogenic land prices linked with the IMAGE framework to address land scarcity and environmental impacts; and 6) partial labour mobility between agricultural and non-agricultural sectors, to assess changes in income distribution.
Keywords: 330; Wirtschaftsmodell; Nachhaltige Entwicklung; CGE-Modelling; Allgemeines Gleichgewicht; Theorie